MONEY LAUNDERING AND CONSTITUTIONAL RIGHTS - A. V. Shashkova (Vestnik MGIMO-Universiteta)
The present article is dedicated to the problem being side-effect and directly related to the anti-money laundering fight: the infringement of the constitutional rights. In 2013 the Constitutional Court of the Russian Federation gave the judgment that the Federal law has a discretionary power to provide in the legislation certain methods preventing terrorism financing and money laundering, obliging financial and other institutions, conducting money transfers to identify their clients. The analysis of such position is given in the present article. The author does not share such position. Analyzing money-laundering especially in the context of renunciation of presumption of innocence, the author shows the deliberate crime. Such deliberate aim shall be stated in the legislation, that means that while concealing, non-reporting, taking or granting funds the person shall mentally understand the illegal origin of such funds: actions shall be dedicated to concealing, covering or assistance in money-laundering. The article analyses Russian and foreign legislation in dealing with the matter, their principles and acts: special legislation on moneylaundering fight, privacy principles, special legislation on “know you customer” programme. The author researches Russian and foreign experience in dealing with anti money-laundering taking into account observance of constitutional rights of people.